1996
DOI: 10.1046/j.1365-2141.1996.d01-1857.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of complement proteins in platelet aggregation by Streptococcus sanguis NCTC 7863

Abstract: We investigated the mechanisms of platelet aggregation by the type strain of Streptococcus sanguis (NCTC 7863). This species is one of the major aetiological agents of infective endocarditis. S. sanguis NCTC 7863 caused aggregation of normal human platelets in vitro following a lag period that varied between donors (7-19 min). Platelet aggregation was dependent on one or more plasma constituents and all the necessary factors gradually became bound to the bacterial surface during the lag period. The length of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Ford et al demonstrated that S. sanguinis strain NCTC 7863 induced aggregation of normal platelets suspended in plasma however removal of plasma proteins abolished platelet aggregation (Ford et al, 1996). The long lag time (12-15mins) of S. sanguinis strain 7863 was progressively shortened by incubating the bacteria in plasma for increasing lengths of time prior to addition to platelets.…”
Section: Platelet-bacterial Interactions: the Streptococcusmentioning
confidence: 99%
“…Ford et al demonstrated that S. sanguinis strain NCTC 7863 induced aggregation of normal platelets suspended in plasma however removal of plasma proteins abolished platelet aggregation (Ford et al, 1996). The long lag time (12-15mins) of S. sanguinis strain 7863 was progressively shortened by incubating the bacteria in plasma for increasing lengths of time prior to addition to platelets.…”
Section: Platelet-bacterial Interactions: the Streptococcusmentioning
confidence: 99%
“…The long lag time is indicative of the time taken for complement assembly [38]. Inactivation of complement by cobra venom or heat treatment abolished aggregation [38]. It is not known precisely how complement activation triggers platelet activation but it is possible that there is a threshold of bacterial-platelet interactions (capable of inducing strong or weak signals) which must be surpassed before triggering platelet aggregation however this remains to be investigated.…”
Section: Indirect Interactionmentioning
confidence: 99%
“…The long lag time is indicative of the time taken for complement assembly [38]. Inactivation of complement by cobra venom or heat treatment abolished aggregation [38].…”
Section: Indirect Interactionmentioning
confidence: 99%
“…The lag time to aggregation in platelet rich plasma (PRP) in response to S. sanguinis 7863 is 7-19 minutes [111] and this variation was correlated to the rate of assembly of the C5b-9 complex on the surface of the bacteria as detected by flow cytometry [110]. Accordingly, the lag time to aggregation using bacterial cells preincubated with plasma before addition to PRP could be progressively shortened with extension of the incubation time [110]. Complement activation can be triggered by antigen-antibody complexes (classical pathway) or by binding of specific complement proteins (alternative pathway) or mannose binding protein (lectin pathway) to the microbial surface.…”
Section: Streptococcal-platelet Interactions -Immunological Responsementioning
confidence: 99%
“…Roles for complement in bacterial-platelet interactions have been demonstrated in Staphylococcal aureus and S. sanguinis [102,107,110]. The lag time to aggregation in platelet rich plasma (PRP) in response to S. sanguinis 7863 is 7-19 minutes [111] and this variation was correlated to the rate of assembly of the C5b-9 complex on the surface of the bacteria as detected by flow cytometry [110]. Accordingly, the lag time to aggregation using bacterial cells preincubated with plasma before addition to PRP could be progressively shortened with extension of the incubation time [110].…”
Section: Streptococcal-platelet Interactions -Immunological Responsementioning
confidence: 99%